2012
DOI: 10.12659/ajcr.882293
|View full text |Cite
|
Sign up to set email alerts
|

Port catheter fracture and migration in Internal Jugular Vein

Abstract: SummaryBackground:Central venous access devices for chemotherapy are being used extensively in patients with cancer. Spontaneous fracture and migration of the catheter is uncommon. We present the uncommon occurrence of a fracture and spontaneous migration of the fragment into the internal jugular vein as a delayed complication of a central venous access catheter implanted for chemotherapy administration.Case Report:A patient with Ewing’s sarcoma of the humerus with metastasis in the lungs underwent placement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 14 publications
(31 reference statements)
0
28
1
Order By: Relevance
“…(1,(16)(17)(18)(19)(20). It was also supposed that factors such as venous flow, negative inspiratory pressure in the thoracic cavity, changes in thoracic pressure with coughing and vomiting, vigorous movement of the upper arms, neck flexion, were thought to lead to migration of fractured material (21,22). In this case, we could not speculate on the cause of migration in our patient.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…(1,(16)(17)(18)(19)(20). It was also supposed that factors such as venous flow, negative inspiratory pressure in the thoracic cavity, changes in thoracic pressure with coughing and vomiting, vigorous movement of the upper arms, neck flexion, were thought to lead to migration of fractured material (21,22). In this case, we could not speculate on the cause of migration in our patient.…”
Section: Discussionmentioning
confidence: 84%
“…Besides that, they may complain of palpitation, cough, dyspnea, thoracic pain, or local swelling and erythema due to serious complications such as infection, pulmonary embolism, arrhythmia, cardiac perforation, ventricular tachydysrhythmia, cardiac arrest, and endocarditis. The first sign of catheter embolization mostly is catheter malfunction precluding fluid injection or blood aspiration and or local pain and subcutaneous swelling at the injection site as seen in our case (2,16,18,22). Therefore, prompt removal of the catheter fragments should be done.…”
Section: Discussionmentioning
confidence: 87%
“…[5]. Fluoroscopy with X-ray is considered the gold standard in retrieval of fractured catheters [4]. Nonetheless, we found that POCUS could be a suitable alternative for accurate detection and retrieval of broken catheter fragments.…”
mentioning
confidence: 83%
“…Various scenarios have been reported in relation to fractured intravenous catheters. Doley et al [4] reported retrieval of a migrated fragment of an implanted central venous catheter through the neck surgically under fluoroscopic monitoring, after its initial detection by X-ray imaging.…”
mentioning
confidence: 99%
“…Catheter detachment is one of the most common complications of implantable venous access systems and has an incidence rate of 0.38–6% [ 1 , 2 ]. This complication can happen over 1 year after port implantation [ 3 ]. A simple chest X-ray can easily reveal catheter detachment.…”
mentioning
confidence: 99%